Microbiological evaluation of fish and seafood available in Huanuco's markets - Vásquez Ampuero, Juan Marco (2018)
The present research work had like objective establishing the fish and seafood's microbiological status expended in Huánuco's markets and flea markets. For such end, they gathered samples of all the dispensing centers such as the markets and flea markets in Huánuco, Paucarbamba and Pilcomarca (n=49), which was processed at the Microbiology's Laboratory of the Veterinary Medical Faculty - UNHEVAL, by the method of the Petrifilm Plate, finding that all the samples were positives to Escherichia coli y Staphilococcus aureus in higher or lower degree depending of the market of origin of the simple. Escherichia coli he identified with an average of 208,880 UFC y Staphilococcus aureus with 259,120 UFC. The Central Market's samples were the most contaminated with E. coli and the flea market Don Pedrito's samples were the most contaminated with S. aureus; in like manner the seafood samples they were but contaminated tan the fishes. It is concluded than fish and the seafood expended in Huánuco's markets, they are contaminated with the microorganisms E. coli and S. aureus; and for the form of expended of these products, they are potential risk for the public health.